KONSTRUKSI MAKNA MALO DALAM KEHIDUPAN SOSIAL DAN BERAGAMA DI MADURA - Fahrul Rozi, Ach. Shodiqil Hafil, (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2021)
Shame (malu in Indonesia or malo in Madura) is closely related to pride for Madurese people. Malo is frequently become postulate to make a deal with violence which is known by carok or fight using weapons to recover that pride. For that, it is necessary to discuss how that exactly the meaning construction of malo for Madurese people is and how that malo creates social ethic and religion in Madura. This study used a qualitative approach with the constructive paradigm, and its technique used visible observation, in-depth interview, documentation and library research. Result of this study showed that malo is such a kind of expression for Madurese people to defend their reputation and pride. All kind of defenses will be taken in order to prevent this malo, even if it is an extreme act which leads to death. This coincides with Madurese philosophy as caâ€™ocaâ€™ which stated that â€œBetter to die than live to bear maloâ€. The big problem will usually occur if this malo was bothered by religious friction and offends the family honor. This malo is a logic consequence as social and religious ethic around Madurese people. Therefore, malo then forms a mindset and gives a positive lifestyle by maintaining social and religiousethic, in order to honor a pride value and human right.Keywords: The meaning construction, malo, caâ€™ocaâ€™, Madurese culture.Abstrak